Article Oh Captain(s)! My Captain(s): On appointing group insolvency practitioner - Pepels, Sid (European Insolvency and Restructuring Journal, 2024)
In this article, the author examines to what extent the European Insolvency Regulation (recast) authorizes Member States' courts to cooperate cross-border through appointing the same insolvency practitioner in insolvency proceedings relating to group companies (a so-called 'group insolvency practitioner'). The author concludes that, within certain boundaries which the article examines thoroughly, courts already can and should make such appointments. The article concludes with various recommendations in order to improve the useful application of this valuable cross-border insolvency tool.